Research projects - Adusei-Owusu, James (Rhodes University, Faculty of Education, Department of Education, 2001)
RESEARCH PROJECTS: 1 RESEARCH PROJECT ONE: A literature review: Constructivism: An alternate approach to teaching and learning. Abstract The constructivist perspectives on learning have helped enhance science educators' understanding of how students make sense of their lived experiences. Constructivism purports to be a transformation of the traditional curriculum. As such this article starts with a brief overview of behaviorism: the scientific approach to education. The main tenets underlying constructivism, how constructivism guides educators to change their classroom practice, and the implications to science teaching have been reviewed. 2 RESEARCH PROJECT TWO (Empirical study): Being Constructive: College students' learning of work and heat as aspects of the energy concept based a constructivist approach. Abstract This study is an extension of a literature review on constructivism as an alternate teaching and learning approach discussed in research project one. It is an empirical study concerning the use of a learning module based on a constructivist approach to develop pre-service student teachers' understanding of work and heat as aspects of the energy concept. The data consisted mainly of transcripts of students' interviews, written responses to questionnaires designed in the form of a worksheet, and comments from non-participant observers and students. The results seem to suggest that a carefully designed learning module based on a constructivist teaching and learning approach may be a valuable tool in developing pre-service student teachers' understanding of work and heat. 3 RESEARCH PROJECT THREE (Empirical study): A College in transition: A case study of the readiness of a college in the Eastern Cape province to implement Outcomes-Based Education in an Education Development centre. Abstract Curriculum 2005 premised on Outcomes-Based Education is the new curriculum framework for South Africa. It signifies a paradigm shift in education from the traditional 'telling-listening' relationship between the teacher and the learner to one that emphasises leamer-centred approach to the teaching process. Teachers, though recognized as crucial to the educational transformation process in the country have also being identified as ill-equipped to meet the challenges posed by Outcomes-Based Education. This study starts with a brief overview of the South African curriculum and the main tenets underlying Outcomes-Based Education. The institutional conditions and whether the lecturers at a college in the Eastern Cape province perceive the need for a change in their classroom practice were also investigated. Bearing in mind the need for further research to validate the findings of this study, positive indicators that emerged from the study suggest the readiness of the college to implement Outcomes-Based Education at the proposed Education Development Centre.
Keywords: Constructivism (Education); Review literature; College students -- Study and teaching; Teaching -- Methods; Competency based education -- Eastern Cape (South Africa)